Energy Technology 2013 : Carbon Dioxide Management and Other Technologies ; Proceedings of Symposia Sponsored by the Energy Committee of the Extraction and Processing Division and the Light Metals Division of TMS (The Minerals, Metals & Materials Society), Held During the TMS 2013 Annual Meeting & Exhibition, San Antonio, Texas, USA, March 3-7, 2013 - Pati, Soobhankar (John Wiley & Sons, 2013)
"This book features a collection of papers on the issues, intricacies, and challenges relating to energy and environmental science. It offers expert coverage of the various technological aspects of sustainable energy ecosystems, including processes that improve energy efficiency and reduce CO2 and other greenhouse emissions. It also addresses the need for sustainable technologies in extractive metallurgy, materials processing, and manufacturing industries with energy efficient technologies. Some additional contributions examine renewable energy sources such as solar, wind, and biomass."--